Design and Manufacture of Plastic Components for Multifunctionality : Structural Composites, Injection Molding, and 3D Printing /: Structural Composites, Injection Molding, and 3D Printing. ([2016]) - Goodship, Vannessa; Middleton, Bethany; Cherrington, Ruth
No abstract available